Genome-wide association studies in asthma - Portelli, Michael A.; Sayers, Ian (Wiley, 2016)
Asthma is a complex respiratory disease, with both genetic and environmental factors contributing to disease susceptibility. Genome-wide association studies (GWAS) have now identified novel risk alleles and loci associated with asthma diagnosis and more recently with clinical subgroups of disease. However, while providing insight into potential disease mechanisms these risk alleles have modest effect sizes and account for a small proportion of the anticipated heritability of asthma. In this article we provide an overview of GWAS in asthma to date including reproducible associations and advances in our understanding of the biology of asthma. In addition we discuss ancestry-specific findings and how genetics may contribute to the development of multiple allergic conditions known as the ‘atopic march’. Finally, we outline the strengths and weaknesses of GWAS and look to future approaches including a greater focus to functional variation and assessment of gene–gene and gene–environment interactions.